Delineating the Origins of Vibrio parahaemolyticus Isolated from Outbreaks of Acute Hepatopancreatic Necrosis Disease in Asia by the Use of Whole Genome Sequencing - Fu, Songzhe; Tian, Huiqin; Wei, Dawei; Zhang, Xiaojun; Liu, Ying (Frontiers in Microbiology, 2017)
Acute hepatopancreatic necrosis disease (AHPND) is an emerging penaeid shrimp disease caused by Vibrio parahaemolyticus. Although V. parahaemolyticus has been isolated and sequenced from several Asia countries, the epidemiological links among the AHPND outbreaks in different locations remain unclear. In this study, we sequenced the genomes of nine strains isolated in China between 2014 and 2016 from four sampling sites in three provinces. Analysis of single nucleotide polymorphisms (SNPs) among the nine isolates yielded an average of 35,519 SNPs per isolate, ranging from 35,001 SNPs to 35,889 SNPs relative to the reference genome FDA_R31. To capture the genetic diversity of V. parahaemolyticus in Asia and Mexico, 93 published genomes were included in the analysis. Phylogenetic analysis divided the 102 isolates into 5 clades from I to V, with the majority belonging to Clade I and Clade II. There were at least 12 independent AHPND related clones. The results indicated that the clones recovered from AHPND affected shrimps in Asia were genomically distinct in various locations and there are no epidemiological links between Asian and Mexico outbreaks. Core genome analysis of pVA-1-like plasmid sequences from V. parahaemolyticus revealed that the AHPND-associated plasmids were also genetically diverse. Homology analysis of the publicly available microbial genomes showed that the conjugative transfer gene clusters of the plasmids in AHPND-causing strains were found in 27 V. parahaemolyticus strains and several other Vibrio sp. from 10 countries including five strains isolated prior to the first identification of AHPND outbreak, indicating that the backbone of AHPND- associated plasmid was widely distributed around the globe. In conclusion, at least 11 origins of AHPND outbreaks were identified; as AHPND-causing plasmid is widely distributed globally, prevention strategies for AHPND need to focus on microbial management in the aquaculture system and establishing ecological friendly aquaculture practices instead of detection of plasmid alone. However, more strains from other Asia countries as well as Mexico need to be included for whole genome sequencing (WGS) for reconstruction of the global transmission and the spread patterns of AHPND.